Peculiarities of Report Generation in University Informational Management Systems - K.A. Fedorchenko (Kherson State University, 2008)
The article analyses problems arising during building special reports in the management systems of the university. To solve the problem is proposed to use metadata, which describe the notions of the user. Also it was done the description of the process of building reports using metalevel with the help of diagrams IDEF0.